HANDLING STRESS THROUGH TAQARRUB ILALLAH AGAINST DRUG ADDICTS AT PONDOK TETIRAH DZIKIR REHABILITATION CENTER - SAHRUL RAMADHAN DARMAWAN; NOVIA FETRI ALIZA (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2023)
This study aims to describe the methods of handling stress through taqarrub ilallah for drug addcict at pondok Tetirah Dzikir Rehabilitation Center. Taqarrub Ilallah is our process as human beings to get closer to Allah including prayer, dhikr, reading the Qur’an, and others. This type of research is qualitative with a case study approach. This research was conducted at Pondok Tetirah Dzikir Rehabilitation Center using case study approach. Data collection was done by observation, in-depth interview, and documentation. The subjects of this study were selected using purposive sampling technique. Which is sampling technique using certain criteria. The criteria for the study subjects were drug addicts, being able to invited to communicate, muslims, adults, and experience, stress at Pondok Tetirah Rehabilitation Center. Data analysis was carried out using Miles and Huberman method by carrying out data reduction, data presentation, and conclusion drawing. The results showed the handling of stress on drug addicts with Islamic approach, namely Taqarrub Ilallah with prayer and dhikr. The prayers performed were fardhu prayer and sunnah prayers. There were two dhikrs used, namely dhikr jahar by using the phrase laa ilaha ilallah and dhikr khofi by mentioning the name of Allah in the heart. Positive change were felt by drug addcits who experienced stress after performing dhikr (dhikr jahar and khofi) and shalat, whis was to get peace of mind. The peacefulness experienced by drug addicts could be interpreted as the reduce stress the experienced early when getting into the Pondok and before intensely performing prayers and dhikr (dhikr jahar and khofi).